Strategi Manajemen Berbasis Keuangan Sebagai Faktor Mitigasi Dalam Penerimaan Keputusan Opini Going Concern Studi Empirik pada Perusahaan Manufaktur di Indonesia - Widhy Setyowati (Conference In Business, Accounting, And Management (CBAM), 2012)
This research is motivated by the Auditing Standard Statement (PSA) number 30 (2001) that requires auditors to evaluate the management plans to overcome financial distress of the company.The management strategy that influence the acceptance of going concern opinion involves financial based strategy such as sale of common stock strategy, issuing new debt or debt restructure, sale of fixed asset and reduction cost strategy. The use of financial condition control variable is based on the assumption that going concern opinion is given only when the company experience financial distress (McKeown et al., 1991; Behn et al., 2001). To test the hypothesis used the logistic regression towards the manufacturer which was registered in Jakarta Foreign Exchange year 2003 – 2007 and experienced financial distress by fulfilling one of the criteria, such as the following: (1) negative work capital, (2) negative equity, (3) negative operating profit and (4) negative net profit. From these criteria are obtained the sample of 275 companies. The result show that sale of common stock strategy and issuing new debt or debt restructure as mitigation factor but sale of fixed asset strategy cannot be used to predict the acceptance of going concern opinion. Otherwise, cost reduction strategy strategy indicates contrary information in going concern opinion acceptance. This evidence gives additional evidence showing that cost of reduction strategy at financial distress company indicates that the company have financial problem.Key words:      going concern opinion, financial distress, financial based strategy financial information.